Locally Advanced Cancer of the Esophagus, Current Treatment Strategies, and Future Directions - Greten, Tim; Rahma, Osama; Duffy, Austin (Frontiers in Oncology, 2012)
For patients with locally advanced esophageal cancer no clear standard of care exists. Notwithstanding several negative phase III studies the data provide support for so-called trimodality treatment and this is probably the most common approach. Even the role of surgery has been questioned. These alternative approaches are set against a changing epidemiological background whereby adenocarcinoma has become the predominant tumor type, at least in the western world. In recent times an emphasis has been placed on the better selection of patients, predominantly based on data that shows a markedly improved survival in those who exhibit a response to neo-adjuvant therapy. In this article we review the major studies and discuss new approaches to the management of patients with locally advanced cancer of the esophagus.